Klasifikasi Penyakit Hipertensi dan Diabetes Berbasis Web Pada Klinik Pratama Rumkitban 01.08.03 Batam - Mira Chandra Kirana; Michel K (Journal of Applied Informatics and Computing, 2021)
The management of outpatient medical records at the Rumkitban Primary Clinic 01.08.03 Batam is still manual and causes many limitations and problems. This problem resulted in the inability of the clinic to run the Chronic Disease Treatment Program (PROLANIS) organized by BPJS-Health. The purpose of the study is to facilitate data processing and then from that data it can be used to classify hypertension and diabetes then the results of the classification are displayed in graphical form. This study discusses 2 diseases, namely hypertension and diabetes. The system uses the C45 Tree Decision Algorithm for automatic data processing. The attributes used are glucose, diastolic, systolic, insulin, and age to support the decision-making system. The system can make a decision whether the patient has hypertension, diabetes or not. The results of this study are the accuracy of classification accuracy in the system for hypertension shows 16.667% accuracy and 83.333% accuracy is not correct, then the calculation of diabetes classification accuracy shows 96.667% accuracy, and 3.333% accuracy is incorrect. This system is integrated with Mysql database to store the results.